Intermittent Hypoxia Mediates Caveolae Disassembly That Parallels Insulin Resistance Development - Varela-Guruceaga, Maider; Belaidi, Elise; Lebeau, Lucie; Aka, Ella; Andriantsitohaina, Ramaroson; Giorgetti-Peraldi, Sophie; Arnaud, Claire; Le Lay, Soazig (Frontiers in Physiology, 2020)
Repetitive complete or incomplete pharyngeal collapses are leading to chronic intermittent hypoxia (CIH), a hallmark feature of Obstructive Sleep Apnea (OSA) syndrome responsible for many metabolic disorders. In humans, an association between OSA and insulin resistance has been found independently of the degree of obesity. Based on our previous work showing that hypoxia applied to adipocytes led to cellular insulin resistance associated with caveolae flattening, we have investigated the effects of CIH on caveolae structuration in adipose tissue. Original exploratory experiences demonstrate that 6 weeks-exposure of lean mice to CIH is characterized by systemic insulin resistance and translates into adipocyte insulin signaling alterations. CIH also induces caveolae disassembly in white adipose tissue (WAT) illustrated by reduced plasma membrane caveolae density and enlarged caveolae width, concomitantly to WAT insulin resistance state. We show that CIH downregulates caveolar gene and protein expressions, including cavin-1, cavin-2 and EHD2, underlying molecular mechanisms responsible for such caveolae flattening. Altogether, we provide evidences for adipose tissue caveolae disassembly following CIH exposure, likely linked to cavin protein downregulation. This event may constitute the molecular basis of insulin resistance development in OSA patients.